Acute kidney injury associated with ingestion of star fruit: Acute oxalate nephropathy: a report of two cases - Hasan, Mahmud Javed; Ray, Nitai Chandra; Islam, Shaikh Shariful; Nahid, Shakil Azam; Shom, Tumpa; Gosh, Proloy; Md Saifullah, Abu Torab (Community Based Medical Journal, 2019)
There are few case reports regarding star fruit's nephrotoxicity and neurotoxicity in chronic kidney disease patients. Star fruit (Averrhoa carambola) is commonly consumed as a herbal remedy for various ailments in tropical countries. However, the dangers associated with consumption of star fruit are not commonly known. Although star fruit induced oxalate nephrotoxicity in those with existing renal impairment is well documented, reports on its effect on those with normal renal function are infrequent. We report two unique clinical presentation patterns of star fruit nephrotoxicity following consumption of the fruit. The first patient is a 52 year-old male diabetic patient who had normal renal function prior to developing acute kidney injury (AKI) after consuming large amount of star fruit juice at once for remedy of diabetes. The second patient, a 27 years old young male who developed acute kidney injury following star fruit ingestion in empty stomach. One case needed 4 sessions of hemodialysis another case recovered over 2 weeks without the need for haemodialysis. Consumption of star fruit, especially on an empty stomach or in a state of dehydration may precipitate acute kidney injury. A history of star fruit ingestion must be actively looked for in patients presenting with unexplained acute kidney injury. The use of star fruit as a therapy for diabetes should be discouraged. CBMJ 2019 July: Vol. 08 No. 02 P: 47-51